Immigrant architects in Brazil: old and new tools for a historiographical discussion - Anat Falbel (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The role of human displacement and migration in cultural processes as well as in the development of form in art and architecture has long been recognized. Throughout the last two decades, however, with the increase of human exchange and experiences of exile, issues concerning dynamics of cultural transfer have come to guide the course of mainstream architectural history. Bringing together old and new ideas surrounding these issues, this article opens up a discussion about the self-perception of Brazilian modern architectural historiography, addressing the role of foreign and immigrant architects in the spread of architectural modernism.